Study of LSPR characteristics of nano bi-pyramid as metals, transition metal nitrides and transparent conducting oxides for bio-molecule detection - Rashid, Md. Hasinur; Ahmed, Syed Sanjid; Haider, Kazi Miraz Al (BRAC University, 2017)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.